2016
DOI: 10.1007/s00382-016-3186-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in the next 30 years: What can a convection-permitting model tell us that we did not already know?

Abstract: probably due to large-scale forced convection is found when considering only the most extreme events (above 50 mm/day). In this case, even the diurnal cycles of precipitation and convection-related indices are similar between resolutions, leading to the conclusion that the 7 km model sufficiently resolves the most extreme convective events. In this region and time periods, the 7 km resolution is deemed sufficient for most assessments of near future precipitation change. However, conclusions could be dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 43 publications
2
49
1
Order By: Relevance
“…Correlations are highest for the winter season (∼ 0.91-0.93). The agreement across resolutions may be attributed to the already relatively high resolution of CLM7 (Fosser et al 2016). In contrast with our findings, Kendon et al (2014) and Ban et al (2015) reported improvements in their convection-permitting simulations at 2-km resolution, especially in summer, compared with the convection-parameterized model at 12-km resolution.…”
Section: Precipitationcontrasting
confidence: 97%
“…Correlations are highest for the winter season (∼ 0.91-0.93). The agreement across resolutions may be attributed to the already relatively high resolution of CLM7 (Fosser et al 2016). In contrast with our findings, Kendon et al (2014) and Ban et al (2015) reported improvements in their convection-permitting simulations at 2-km resolution, especially in summer, compared with the convection-parameterized model at 12-km resolution.…”
Section: Precipitationcontrasting
confidence: 97%
“…Ban et al (2015), in contrast, found that the intensities of both hourly and daily extreme precipitation scale with temperature at the CC rate in a 2.2 km resolution RCM simulation over the Alps. Comparing a 7 km convection-parameterising model with a convection-permitting 2.8 km resolution RCM in southern Germany, Fosser et al (2016) found similar climate change signals for both models. If only wet days are considered the scaling reaches super CC rates for hourly precipitation in the convection-permitting model.…”
Section: Discussionmentioning
confidence: 75%
“…With respect to the secondary hazards that can be triggered by heavy precipitation, a review compiled by Gariano and Guzzetti (2016) reports an increased risk for landslide fatalities in regions where climate change increases the frequency and intensity of severe precipitation. In contrast, the response of river floods to climate change is less homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with a smaller sample, one event per year on average, the parameters of a larger sample must not deviate beyond the uncertainty bounds of the smaller sample. We follow Coles et al (2001) approach as implemented in the R library "ex-tRemes" (Gilleland and Katz, 2016) and investigate the appropriate threshold for the different durations of one member of the historical period for each RCM and in all subregions. To determine the threshold at a 95 % confidence level, we go through all grid points of each subdomain and find the average number of events per year that is rejected by at most 5 % of the grid points.…”
Section: Extreme Value Theory Approachmentioning
confidence: 99%